Happier, faster: Developmental changes in the effects of mood and novelty on responses. Issue 1 (January 2016) - Schomaker, Judith; Rangel-Gomez, Mauricio; Meeter, Martijn
Positive mood ameliorates several cognitive processes: It can enhance cognitive control, increase flexibility, and promote variety seeking in decision making. These effects of positive mood have been suggested to depend on frontostriatal dopamine, which is also associated with the detection of novelty. This suggests that positive mood could also affect novelty detection. In the present study, children and adults saw either a happy or a neutral movie to induce a positive or neutral mood. After that, they were shown novel and familiar images. On some trials a beep was presented over headphones either at the same time as the image or at a 200-ms stimulus onset asynchrony (SOA), and the task of the participant was to detect these auditory targets. Children were slower in responding than adults. Positive mood, however, speeded responses, especially in children, and induced facilitatory effects of novelty. These effects were consistent with increased arousal. Although effects of novelty were more consistent with an attentional response, in children who had watched a happy movie the novel images evoked a more liberal response criterion, suggestive of increased arousal. This suggests that mood and novelty may affect response behaviour stronger in children than in adults.